CD200 immune checkpoint expression is associated with inferior outcome in multiple myeloma patients treated with anti-CD38 monoclonal antibodies - Djamila Chemlal; Camille Pochard; Valentin Jacquier; Angélique Bruyer; Ludovic Gabellier; Léa Fornero; Clément Vempère; Amélie Machura; Guilhem Requirand; Nicolas Robert; Caroline Bret; Guillaume Cartron; et al. (OncoImmunology)
In multiple myeloma (MM), the anti-CD38 monoclonal antibody Daratumumab has become essential in the therapeutic arsenal, although very few predictive factors of response to Daratumumab have been identified in clinical studies. We have prospectively collected biological data from 97 patients treated with Daratumumab in first line or at relapse in our center between 2016 and 2020. These data included multiparameter flow cytometry phenotype (CD200, CD117, CD56, CD38, CD45, and CD27), cytogenetic, and transcriptomic gene expression profiling (GEP) of tumor plasma cells before treatment with Daratumumab. We first looked for predictive factors of response to Daratumumab. We found that high CD56 expression and CD45 expression were significantly associated with better progression free survival (PFS) whereas high CD200 expression was significantly associated with poorer PFS. Then, we showed that the CD200-CD200R immune synapse is responsible for a decrease in Daratumumab response through the alteration of NK cells’ activity. Finally, we demonstrated that inhibition of CD200 increase response to Daratumumab in MM patient samples, highlighting its potential as a predictive biomarker for Daratumumab response and as a possible therapeutic target in combination with Daratumumab. This study is the first to identify phenotypic and molecular factors’ predictor of response to Daratumumab.